EFEKTIVITAS MODEL PEMBELAJARAN TWO STAY TWO STRAY PADA MATERI BILANGAN BERPANGKAT DI SMP AL-WASILAH - Mahsus Mahsus; Zainuddin Zainuddin; Dwi Ivayana Sari (SIGMA, 2021)
This study aims to determine the ability of teachers to manage learning, student responses, student learning completeness with the two stay two stray learning model on the material of rank numbers. The type of research used is descriptive quantitative. The sample used is class IX SMP Al-Wasilah. Data analysis used data analysis on the ability of teachers to manage learning, analysis of student response data and analysis of student learning outcomes test data. Based on the results of data analysis shows that the results of the data analysis of the average score of the ability of teachers to manage learning using the two stay two stray learning model is 4.44. The data obtained on the level of teacher ability to manage learning is in the good category. Data analysis of the average score of students' positive responses to the two stay two stray learning model was obtained at 96.4%. The positive response data obtained by students are in the category of strongly agree. The results of the percentage of students' learning completeness classically were obtained at 81.25%. Thus, the classical student learning completeness data is >80%. It can be concluded that the two stay two stray learning model is effective.